Analysis of the Role of Learning Methods in Improving Elementary School Students' Social Skills - Desyrimayani, Desyrimayani; afifah, Dhea; Nurfaria, Irna; Sintia, Sintia; Syafruddin, Syafruddin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This article analyzes the role of learning methods in improving elementary school students' social skills. Social skills are an important aspect of children's development that allows them to interact and communicate effectively with other people. This article reviews several learning methods that have been proven effective in improving social skills, such as discussion methods and role playing. This article also discusses the importance of creating a learning environment that supports and encourages positive interactions among students. The results of the analysis show that using appropriate learning methods can help elementary school students develop communication, collaboration, empathy and assertiveness skills that equip them to interact well in various social situations.